Plasma Big Endothelin-1 Levels and Long-Term Outcomes in Patients With Atrial Fibrillation and Acute Coronary Syndrome or Undergoing Percutaneous Coronary Intervention - Lyu, Si-qi; Zhu, Jun; Wang, Juan; Wu, Shuang; Zhang, Han; Shao, Xing-hui; Yang, Yan-min (Frontiers in Cardiovascular Medicine, 2022)
Background: This study aimed to evaluate the association between plasma big ET-1 levels and long-term outcomes in patients with atrial fibrillation (AF) and acute coronary syndrome (ACS) or undergoing percutaneous coronary intervention (PCI). Methods: A total of 930 patients were enrolled and followed up for a median duration of 2.3 years. According to the optimal cutoff of big ET-1 for predicting all-cause death, these patients were divided into two groups. The primary endpoints were all-cause death and net adverse clinical events (NACE). The secondary endpoints included cardiovascular death, major adverse cardiovascular events (MACEs), BARC class ≥3 bleeding, and BARC class ≥2 bleeding. Cox regressions were performed to evaluate the association between big ET-1 and outcomes. Results: Based on the optimal cutoff of 0.54pmol/l, 309 patients (33.2%) had high big ET-1 levels at baseline. Compared to the low big ET-1 group, patients in the high big ET-1 group tended to have more comorbidities, impaired cardiac function, elevated inflammatory levels, and worse prognosis. Univariable and multivariable Cox regressions indicated that big ET-1 ≥0.54pmol/l was associated with increased incidences of all-cause death [HR(95%CI):1.73(1.10-2.71),p=0.018], NACE [HR(95%CI):1.63(1.23-2.16),p=0.001], cardiovascular death [HR(95%CI):1.72(1.01-2.92),p=0.046], MACE [HR(95%CI):1.60(1.19-2.16),p=0.002], BARC class ≥3 [HR(95%CI):2.21(1.16-4.22),p=0.016], and BARC class ≥2 bleeding [HR(95%CI):1.91(1.36-2.70),p<0.001]. Subgroup analysis indicated consistent relationships between the big ET-1 ≥0.54pmol/l and the primary endpoints. Conclusion: Elevated plasma big ET-1 levels were independently associated with increased risk of all-cause death, NACE, cardiovascular death, MACE, BARC class ≥3 bleeding, and BARC class ≥2 bleeding in patients with AF and ACS or undergoing PCI.